The Role of Purchase Decisions in Mediation the Influence of Price Perception, Convenience and Promotion on Consumer Satisfaction (Study Case for Shopee Users in Malang City) - Agam Rizkiyan; Nur Hidayati; Eka Farida (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Study this aim for analyze role decision purchase in mediate influence perception price, convenience and promotion to satisfaction consumer. Population study this is Shopee users in Malang City. In study this technique taking sample use purposive sampling so that set respondent as many as 100 respondents. Method analysis the data is quantitative descriptive. Analysis quantitative conducted with use SmartPLS. In study this get results that perception price and promotion take effect significant to decision purchase, convenience no take effect to decision purchase, decision purchase no take effect to satisfaction consumer, perception price and promotion no take effect to satisfaction consumer, convenience take effect significant to satisfaction consumer. Purchase decision no capable mediate influence perception price, convenience and promotion to satisfaction consumer.